Analysis of the readiness and potential of Nias Island tourist destination - Ziliwu, Metani Nibeli; Rahmiati, Filda; Geonadhi, Felix; Mangkurat, R. Stevanus Bayu (Interaction, Community Engagement, and Social Environment, 2024)
Background: Nias Island has tourism potential that can be enjoyed by visiting tourists. This island is famous for hosting the World Surfing League (WSL). However, Nias Island is struggling with accessibility problems and facilities that are not up to standard, these problems need to be fixed to encourage tourist destinations on Nias Island. Therefore, this study aims to determine the potentials of Nias Island as a tourist destination and to provide solutions for Nias Island, especially in the areas of accessibility and facilities. Methods: This study uses a qualitative method. This study uses the observation method because it is in accordance with the events in the field. Findings: The results of this study are that Nias Island has a lot of tourism potential in the fields of nature, cultural heritage, and natural tourism products. Conclusion: There are several suggestions that can be made to improve the quality of tourist attractions on Nias Island in terms of accessibility (providing road signs) and facilities (improving cleanliness and maximizing existing facilities around tourist attractions). Novelty/Originality of this Study: The study on Nias Island’s tourism potential is novel in its comprehensive approach to addressing both the island's untapped natural and cultural attractions and the critical issues of accessibility and facility deficiencies. By providing targeted solutions to improve road signs, cleanliness, and the overall quality of tourist facilities, this research